Fermentable Oligo-, Di-, Monosaccharides and Polyols and cancer risk in the NutriNet-Santé cohort. (20th October 2021) - Debras, C; Chazelas, E; Srour, B; Julia, C; Schneider, É; Agaësse, C; Druesne-Pecollo, N; Hercberg, S; Deschasaux-Tanguy, M; Touvier, M
Abstract: Background: Fermentable Oligosaccharides, Disaccharides and Monosaccharides And Polyols (FODMAPs), which are found in a variety of foods (dairy products, fruit, legumes, refined grains, sugary beverages, etc.) have been involved in risk for gastrointestinal disorders. In view of their pro-inflammatory potential and their interactions with the gut microbiota, their contribution to the etiology of other chronic diseases such as cancer has been postulated. However, no epidemiological study has investigated this hypothesis so far. Our objective was to investigate the associations between FODMAP intake (total and by type) and cancer risk (overall, breast, prostate and colorectal). Methods: 104, 909 French adults from the NutriNet-Santé prospective cohort (2009-2020) were included (median follow-up time=7.7y). FODMAP intakes were obtained from repeated 24h-dietary records linked to a detailed food composition table. Associations between FODMAPs and cancer risks were assessed by Cox proportional hazard models adjusted for a large range of lifestyle, sociodemographic and anthropometric variables. Results: Total FODMAP intake was associated with increased overall cancer risk (n = 3, 374 incident cases, Hazard Ratio for quintile 5 vs quintile 1=1.21, 95% confidence interval 1.02-1.44, P-trend=0.04). Oligosaccharides seemed to be the FODMAP type particularly associated with cancer risk: a trend was observed for overall cancer (HR = 1.10 (0.97-1.25) P-trend=0.04) and colorectal cancer (n = 272, HR = 1.78 (1.13-2.79) P-trend=0.02). Associations remained stable across a series of sensitivity analyses. Conclusions: Our findings suggest a potential role of FODMAPs in cancer onset. Further epidemiological and experimental studies are needed to confirm these results and provide data on the potential underlying mechanisms. Key messages: In this large-scale prospective cohort of French adults, FODMAP intake was associated with increased cancer risk. These associations need to be studied in other prospective cohorts, in order to clarify FODMAPs role in cancer development.